أحكام الحضاةً في الفقه الإسلاهي هقارةً بقاوًى الأحوال الشخصية الليبي)دراسة فقهية مقارنة(Ahkam Al-hadhonah Fi Al-fiqh Al-Islamy Muqoranah Bi Qonun Al Wa As-Syakhshiyah Al-aliby - Saad, Tahani Mahmoud; , Dr. M. Muinudinillah Basri, M.A; , Dr. M. Abdul Kholiq Hasan, M.A., M.Ed (2014)
This message looking for a nursery in the provisions of Islamic jurisprudence and Libyan law. This thesis is applied for Islamic Law master Program, Muhammadiyyah University of Surakarta. Arranged by: Tahani Mahmoud Saad. NIM: O20012000. Supervised by Dr.Muhammad Muinudinillah Basry, MA and Dr. Mohamed Abdel Khalik Hassan. Year 2014 AD - 1435 H. This message qualitative research office, which made me posting this research, is the large number of issues on the nursery in the courtyard of the judiciary in the Libyan society and the problems of supply in the following research: how to reconcile the law with the Libyan Islamic jurisprudence in the door of the provisions of the nursery? Where my goal is to liberate accountable nursery comparative study of Islamic jurisprudence with Are said the four schools with Libyan law. The approach taken by the research methodology Allosteric analytical comparison. Find the most important findings: that the law of personal status Libyan nursery door is consistent with the Maliki school except for some cases, where interest requires otherwise, because throughout the nursery are the interests of the child and because the interest on the introduction of all other interests. As it became clear that the Libyan law leave it to the judge in some cases, in the interest of the child and for the judge to rule it under the authority and with what is agreed with the doctrine the militant also criticized the Libyan law did not address some of the texts in the nursery but there is a text item number (72, paragraph b) mentions where if there is no legislative text can be applied he is condemned under Islamic Sharia principles most relevant to the provisions of this law and this indicates that the Personal Status law in the Libyan nursery door with a conciliator Islamic jurisprudence because originally derives its legitimacy from Islamic jurisprudence.